¿La hemoglobina, es un marcador genético invariable? Hallazgos en la gallina criolla andina. - León-Velarde, Fabiola; Mejía, Olga; Espinoza, Daniel; Larrick, Jim; Monge, Carlos (Acta Andina, 2025)
Chicken (Gallaus gallus) were introduced in South America during the Spanish conquest and therefore their adaptation time to high altitude is approximately 500 years. A group of chicken from the Peruvian Andes (4,000m) carrying a high hemoglobin-oxygenaffinty has been identified and reproduced at sea level. The hemoglobin-oxygenaffinity (P 50) has been determined, by a mixing technique, in whole blood and in phosphate-free hemoglobin solutions before and after the addition of inositol hexaphosphate (IHP). The Andean chicken alpha and beta globin genes were sequenced. A mutation Thr → Ser in position 69 of the β chains of Hb A has been found. The addition of IHP to the significantly less in the sea-level chicken (42.2 torr) suggesting that the high-affinity hemoglobin is probably dependent on a moleculara change affecting the allosteric regulation. These findingshow the unprecedent observation in nature of a hemoglobin genetic change in an exceptionally short evolutionary time in a sea-level terresrial bird. This observation also shows that the same species can be differentiated from its sea-level counterpart by a genetic change in the Hb function as a reflect of its structure.